2019
DOI: 10.1127/pip/2019/0081
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of harmful algal blooms on the aquaculture industry: Chile as a case study

Abstract: Harmful algal blooms (HABs) of toxin-producing microalgae, mainly Alexandrium catenella, Dinophysis spp., and Pseudonitzschia australis, cause the severe illnesses referred to as paralytic, diarrheic, and amnesic shellfish poisoning. They therefore threaten the sustainable exploitation of bivalves, including in northern and southern Chile, sites of intensive shellfish aquaculture but also recurrent HABs. Exceptionally large blooms of the genera Pseudochattonella and Karenia recently occurred in the Patagonian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 42 publications
0
107
0
Order By: Relevance
“…Harmful algal blooms (HABs) are intense algal proliferations that can profoundly disrupt the habitat where they occur via the production of high biomass accumulation, which causes oxygen depletion and the production of high amounts of toxins [1,2]. HABs induce detrimental effects on marine organisms, humans, environments and economies [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Harmful algal blooms (HABs) are intense algal proliferations that can profoundly disrupt the habitat where they occur via the production of high biomass accumulation, which causes oxygen depletion and the production of high amounts of toxins [1,2]. HABs induce detrimental effects on marine organisms, humans, environments and economies [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Zonal and meridional surface winds from QuikSCAT (1999QuikSCAT ( -2009, ASCAT (2007ASCAT ( -2015, and ERA5 reanalysis (1999-2015) were used to apply EOF analysis (Emery and Thomson, 1998;Kaihatu et al, 1998) to determine the modes of variability that dominated the spatiotemporal behavior of the wind field in the eastern austral Pacific Ocean. Before computing the EOFs, long-term means and linear trends were removed for each scatterometer (QuikSCAT and ASCAT) and the reanalysis product (ERA5) separately.…”
Section: Discussionmentioning
confidence: 99%
“…9). Studies have shown that, when onshore ET occurred, downwelling conditions prevailed and particulates were transported to the coast (Stewart, 2002), favoring the retention of eggs and larvae in the coastal zone (Epifanio and Garvine, 2001;Garland et al, 2002). It has also been shown that, when offshore ET occurred, upwelling processes dominated along the coastline, favoring primary biological production (Escribano et al, 2016;Iriarte et al, 2012;Montero et al, 2007).…”
Section: Oceanic-atmospheric Interactionsmentioning
confidence: 99%
“…Although mechanisms of HAB are not fully elucidated, the frequency of HAB and their intensity of consequences are expected to increase in the future as global ocean temperatures rise [ 6 , 7 ]. Chile, a country in the southern Pacific Ocean, has been severely affected by HABs damaging the well-known aquaculture and fishery industries with broad socio-ecological impacts [ 8 ]. Blooms of Pseudochattonella verruculosa and Alexandrium catenella during the austral summer of 2016 were particularly severe, causing the largest fish and bivalve mortality rates ever recorded in the world.…”
Section: Introductionmentioning
confidence: 99%